Association between physical performance tests and external load during scrimmages in highly trained youth ice hockey players - Byrkjedal, P. T.; Bjørnsen, T.; Luteberget, L. S.; Lindberg, K.; Ivarsson, A.; Haukali, E.; Spencer, M. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To investigate the relationship between physical performance tests and on-ice external load from simulated games (scrimmages) in ice hockey.